Pan-Africanism : political philosophy and socio-economic anthropology for African liberation and governance, Caribbean and African American contributions. - Kinni, Fongot Kini-Yen (Langaa Research & Publishing, 2015)
This Book is the outcome of a long project begun thirty years ago. It is a book on the makings of pan-Africanism through the predicaments of being black in a world dominated by being white. The book is a tribute and celebration of the efforts of the African-American and African-Caribbean Diaspora who took the initiative and the audacity to fight and liberate themselves from the shackles of slavery. It is also a celebration of those Africans who in their own way carried the torch of inspiration and resilience to save and reconstruct the Free Humanism of Africa. As a story of the rise from the shackles of slavery and poverty to the summit of Victors of their Renaissance Identity and Self-Determination as a People, the book is the story of African refusal to celebrate victimhood. The book also situates women as central actors in the Pan-African project, which is often presented as an exclusively masculine endeavour. It introduces a balanced gender approach and diagnosis of the Women actors of Pan-Africanism which was very much lacking. The problem of balkanisation of Africa on post-colonial affiliations and colonial linguistic lines has taken its toll on Africa's building of its common identity and personality. The result is that Africans are more remote to each other in their pigeon-hole-nation-states which put more restrictions for African inter-mobility, coupled by education and cultural affiliations, the communication and transportation and trading networks which are still tied more to their colonial masters than among themselves. This book looks into the problem of the new wave of Pan-Africanism and what strategies that can be proposed for a more participatory Pan-Africanism inspired by the everyday realities of African masses at home and in the diaspora. This book is the first book of its kind that gives a comprehensive and multidimensional coverage of Pan-Africanism. It is a very timely and vital compendium.